Yobs, Dahls reunite (Raton Range Raton, New Mexico, 1984)
Newspaper Article on a big family reunion between the Yob and Dahls family.
Families attending were: Alma and Lino Ghiglieri, Albert and Erma Sculte, Ed and Mary Dahl and Modesta Yob. Paul, Kathy, Steve and Tim Schulte. Robert, Georgie and Brian Schulte, James Diane and Felicia Schulte. John, Geraldine ad John L. Gooden. Tricia Sizemore and Dewey and Lynn Maire Wilson. Luther, Karen, Lisa, Kara, Todd, and Ian Johnson. Bobby, Treva Mary, Suzanne and Eric Adolf. Marion Yob, Tom IV, Linda Tom III and Jamie Walkins. Earl Wade, Pam and Tate Gordon Berlier. Jehmiel, Melanie Sunnie, Tenniel and Joshua Sawaya. Shaheen, Martha, Shannon and Mark Sawaya. Jeff Romero, Bruno and Doris Bergamo. Ed, Judy, Sam and Tricia Bergamo. Fred and Mary Bergamo. John, Peggy and Mary Bizyak. Pete, Ruthie and Frances Martinez,. Bob Geldhouse. E.K. Bernard and Clara. Graham Alberta, Richard and Wayne Barger. Joe Vigil. John, Pam, Jill and John Jr. Milkovich. David, Patricia, Annie and Amanda Butt. Nancy Ellaine and Emily Avita. Louis and Emily Bergamo.
Master list item #: 12
File location is in the Raton File Cabinet
Keywords: Golden Eagle Lodge; Lady of Sorrows Catholic Church; Local History; Biography; Life and Customs; Family; Reunion; Raton, New Mexico; Red River, New Mexico; Aurora, Colorado; Albuquerque, New Mexico; Santa Fe, New Mexico; Amarillo, Texas; Albuquerque, New Mexico; Texarkana, Texas; Sherman, Texas; Laden, Kansas; Laken, Kansas; Pueblo, Colorado; Cimarron, New Mexico; Trinidad, Colorado; Questa, New Mexico; Los Alamos, New Mexico